Biofortification: The Second Global Conference - International Food Policy Research Institute (2010)
The Second Global Consultation on Biofortification, to be held in Kigali, March 31-April 2, 2014, aims to deepen engagement with major actors in the global effort to improve nutrition and public health through nutrient-rich crops. The website also contains material from the First Global Conference on Biofortification, held November 9-11, 2010 in Washington, DC.